Proveniência, paleogeografia e sedimentologia dos depósitos do Grupo Itararé no extremo sul da Bacia do Paraná - Tedesco, Julia (Universidade do Vale do Rio dos Sinos, 2019)
Fine-grained rhythmite is a recurrent sedimentary facies in glacially-influenced marine and lacustrine sequences throughout geological time. Paleoenvironmental interpretation of these ancient deposits has been a challenged since similar rhythmites may have formed in different depositional contexts. In the Paraná Basin, the Itararé Group contain numerous successions of fine-grained rhythmites, deposited in the Carboniferous during the Late Paleozoic Ice Age (LPIA). Thus, the purpose of this study is: (i) to characterize sedimentological aspects of different rhythmites of the Itararé Group in southern Paraná Basin, and (ii) interpret their depositional environments. The described rhythmites are characterized by the intercalation of fine-grained sandstones and siltstones with clay and clayey siltstones. We have identified two distinct types of rhythmites based on the contact between couplets, couplets thickness, sedimentary structures, and geochemical proxies. Rhythmites type 1 is characterized by intercalation of very fine-grained sandstone/siltstone (60-90%) with claystone (40-10%) and normal grading. Rhythmites type 2 is characterized by couplets of siltstone (50%) and claystone (50%), with a sharp contact within couplets. Rhythmites type 1 is interpreted as turbidity current deposits and type 2 as distal deposits of hypopycnal flow. Geochemical proxies suggest deposition of the rhythmites under marine conditions, in a period of rising temperatures and humidity, and with intensified chemical weathering. These paleoenvironment characteristics are in agreement with the interglacial period. The preservation of thick rhythmite successions of the Itararé Group in the southern basin was controlled by the constant creation of accommodation space inside paleovalleys.
Keywords: Grupo Itararé; Pensilvaniano; Itararé Group; Pennsylvanin; Late paleozoic ice age; ACCNPQ::Ciências Exatas e da Terra::Geologia